The Relationship Between Infertility and Infection with Clarithromycin Resistant Strain of Helicobacter Pylori in Iraq - Abid, Shiamaa G.; Aboud, Rana S. (Iraqi Journal of Science, 2020)
The relationship between infertility and Helicobacter pylori infection was investigated; samples from thirty-five infertile patients (aged 20-49 years) were collected from Kamal Al-Samaraei hospital , Baghdad, Iraq during the period from the first of February until April 2018. These patients were compared with 10 apparently fertile individuals who served as a control. The study was carried out to detect the DNA of H.pylori in both serum and seminal fluid of male infertile patients and for the control group by Real-Time Polymerase Chain Reaction (RT-PCR) technique. The results revealed that there was a significant difference (P<0.01) in the detection of DNA of H.pylori between patients and control groups. thereby the percentage level of H.pylori DNA in serum was 80% and in the seminal fluid was 0 %. As a result, we strongly suggest that the infection with H. pylori plays an important role in male infertility.